The Political Economy of International Education: A Critical Discussion - Wu, Wenxi (Critical Education, 2022)
As educational sectors and stakeholders are increasingly engaged in the practice of international education, there have been many discussions regarding two persisting issues with the practice, which can be summarised as Western-centrism and elitism. Applying concepts from the study of political economy, this paper analyses major political constraints underlying these two challenges. The paper suggests that the origin of these political constraints is a Western-dominated neoliberal world order, with powerful effects on the educational choices made by advantaged groups in non-Western societies. The analysis highlights a political-economic cycle based on the West’s export of educational products in exchange for human and economic capitals, which sustains the current ecology of international education. The paper also discusses possible ways to redress the political constraints for international education to be more inclusive and equitable. It concludes with notes on new challenges underway and their effects on the future directions of international education.